Penyusunan Usulan Bahan Ajar Kaiwa Berdasarkan Hasil Survei terhadap Mahasiswa Bahasa Jepang UNJ - Yuniarsih (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2011)
The preparation of these materials are substantially follow the need of students and prediction of material needed. A proposed teaching materials starting with Tasuku Kaiwa Senkoukei (Task early) and ends with matome (summary) in which load characteristic of spoken language in Japanese such as differences in the expression in accordance with the speaker, the structure of conversation, the language of men and women, aizuchi, iisashi, shouryaku, expression and fuction of non-verbal communication.